Katechismus-Andachten (1656). Kritische Ausgabe und Kommentar. Kritische Edition des Notentextes - Steiger, Johann Anselm (Neudrucke deutscher Literaturwerke. N. F., 2016)
The Catechism Devotions is comprised of 50 spiritual songs that impart all of the material in Luther's Small Catechism in vocal form. They are regarded as an important milestone in early modern theologia catechetica that aimed at an elemental presentation of the liturgy.